Successful salvage surgery followed by second ALK–TKI after alectinib failure in a patient with ALK-positive NSCLC - Hiroshi Hashimoto; Kazuyuki Komori; Koji Kameda; Shinichi Taguchi; Yuichi Ozeki (Surgical Case Reports)
Abstract Background Anaplastic lymphoma kinase (ALK)–tyrosine kinase inhibitors (TKIs) have been approved for the therapy of locally advanced non-small cell lung cancer (NSCLC) caused by ALK rearrangement. However, its treatment after failure of initial ALK–TKI therapy remains controversial. Case presentation A 47-year-old woman with a hemosputum was diagnosed with adenocarcinoma of the left lung (cT2bN3M0, stage IIIB). Gene mutation analysis indicated positive ALK translocation. Alectinib was selected as the first-line treatment. Although the treatment effect was determined as a partial response, the main tumor regrew. Alectinib was discontinued, and salvage surgery was performed without causing morbidity. The pathological diagnosis was pleomorphic carcinoma without lymph node metastasis (yp-T2bN0). After surgery, lorlatinib was administered as the second-line treatment for 8 months until the patient could not tolerate continuation. Computed tomography scan revealed no lung cancer recurrence 14 months after discontinuation. Conclusions Our experience with this case suggests that salvage surgery after alectinib treatment followed by lorlatinib therapy may be effective for initially unresectable ALK-positive NSCLC.